Enhanced transient response and seamless interconnection of multi‐microgrids based on an adaptive control scheme - Aisha M. Pasha; Mohamed Shawky El Moursi; Hatem H. Zeineldin; Vinod Khadkikar; Ehab F. El‐Saadany; Mohamed Al Hosani; Ahmed. F. Bendary (IET Renewable Power Generation, 2021)
Abstract The interconnection of microgrids to form a network known as the multi‐microgrid (MMG) brings higher resilience and support in providing power to the loads. The dynamic response during interconnection is usually bypassed with the addition of synchro‐checkers installed on all the microgrids and the exchange of critical setting points between the microgrids prior to interconnection via a low‐bandwidth communication. This paper introduces a novel decentralized framework for maintaining the voltage and frequency of the microgrids within permissible operating range during the interconnection. The proposed control strategy is triggered when the microgrids violate the defined states of operation and the fast control action from each type of Distributed Generation (DG) in the microgrid is designed to tackle the transients in the voltage and frequency in order to regulate them within the IEEE standards. Moreover, the study is extended to evaluate the performance of interconnecting single microgrids to form MMG using the decentralized proposed control strategy and then sectionalizing the MMG back into separate autonomous microgrids. The results have been verified using PSCAD/EMTDC. The proposed control strategy demonstrates superior performance and simplicity for carrying out the energy management for interconnecting and sectionalizing of MMG without any kind of communication and synchro‐check infrastructures.